Prototype of a glass to administer liquid to newborns - Suzana Lopes de Melo; Luciano Borges Santiago; Cristiane Faccio Gomes; Ana Lúcia de Assis Simões; Virgínia Resende Silva Weffort (Rev Rene)
The aim of this study was to describe the evaluation of health professionals about a prototype glass to administer liquids to newborns. It was a descriptive, exploratory study, which was carried out at the maternity of a university hospital, in Uberaba, MG, Brazil. Semi-structured questionnaires were applied to 75 health professionals, after administering a glass of milk to newborns, in the months of July and August, 2011. Quantitative data were analyzed descriptively and subjected to qualitative content analysis, three categories emerged: positive aspects, with 269 of the register units; negative aspects, with 11 units and suggestions to improve the glass, with six. Statistical analysis showed that the concepts ‘good’ and ‘excellent’, related to the prototype glass, presented rates over 90%. The perception of the participants demonstrated a positive evaluation of the prototype glass, which proved to be a practical tool, the design and safe material for the execution of the ‘technique of the little glass’.